Terrorism as process narratives: a study of pre-arrest media usage and the emergence of pathways to engagement - Holbrook, Baldvin Donald (Terrorism and political violence, 2019)
Terrorism is a highly irregular form of crime where multiple factors combine to create circumstances that are unique to each case of involvement, or attempted involvement, in terrorist violence. Yet, there are commonalities in the way in which efforts to become involved unfold as processes, reflected as sequential developments where different forces combine to create conditions where individuals seek to plan acts of violence. The best way to frame this involvement is through analytical approaches that highlight these procedural dimensions but are equally sensitive to the nuances of each case. Analysing pre-arrest media usage of convicted terrorists, this paper focuses on the ways in which belief pathways and operational pathways interact in five distinct cases of terrorist involvement in the UK in what are termed “process narratives.”